Atypical bilateral papilledema during the puerperium: a case report - Ligang Jiang; Xin Jiang; Ailian Li; Mengting Liu; Zhe Zhang; Yuhua Tong (Frontiers in Medicine, 2025)
BackgroundTo analyze a case of atypical bilateral papilledema in a puerperium woman, and to explore the pathogenic mechanism of pregnancy-related physiological changes, blood hypercoagulable state, immune abnormalities and abnormal structure of intracranial venous sinus, so as to provide reference for early diagnosis and intervention of similar cases.Case reportA 28-year-old woman, 3 days post-operative from a cesarean section, presented at the hospital with decreased vision in her right eye. An examination revealed bilateral papilledema. She did not have typical symptoms like dizziness, headache, or pulsatile tinnitus. During pregnancy, she had taken hydroxychloroquine orally for 5 months due to elevated immune indexes. She also received anticoagulant therapy for lower extremity venous thrombosis a month prior and had a history of cerebrospinal fluid leakage repair for intracranial hypotension syndrome a year ago. Fundus photography and OCT showed bilateral papilledema and macular edema in the right eye, with slightly enlarged physiological blind spots in both eyes. Her pre-pregnancy BMI was 16.5, and postpartum BMI was 22. Laboratory tests indicated a D-dimer level exceeding 20 mg/L and abnormal immune indicators. Ophthalmic color Doppler ultrasound demonstrated bilateral optic nerve sheath widening, with measurements of 0.625 cm on the right and 0.590 cm on the left, suggesting potential elevated intracranial pressure. MRV detected stenosis in the right distal sigmoid sinus and proximal transverse sinus, while the left sigmoid sinus and transverse sinus were not visualized. The patient was diagnosed with increased intracranial pressure caused by multiple factors. Treatment with mannitol to reduce intracranial pressure, along with anticoagulation and other supportive and symptomatic treatments, was administered. After 1 week, macular edema in the right eye subsided, vision improved, and bilateral papilledema slowly improved.ConclusionThis case provides multi-dimensional clinical evidence for the differential diagnosis of puerperium papilledema. For patients with low BMI and atypical symptoms of bilateral papilledema during puerperium, it is necessary to be alert to multiple pathogenic factors. It is recommended to preferentially screen intracranial venous sinus lesions and detect immune indicators by imaging. Ocular ultrasound can be used as a non-invasive screening method for intracranial hypertension.